The Role of Internal Audit Practice to Promote Good Governance in Public Institution of Ethiopia: The Case of Jimma Zone (Global Journal of Management and Business Research, 2018)
The purpose of this study is to examine the role of internal audit practice in promoting good governance in public institution of Ethiopia a case of Jimma zone This study is apparently up to now have been not empirically examined using inferential statistics in the Jimma zone specifically and rarely examined in Ethiopia generally Primary data was obtained through the administration of structured questionnaire to purposively selected respondents comprising internal auditors and managers from14 Were das and 2 town administrations of finance and economic development offices that are expected to represent all other sectors A total of 132 respondent participated in the study Data obtained was analysed using correlation analysis and multiple regression technique According to the regression output Formal mandate and Standards for the Professional Practice Competent staffs Organizational independences and objectivity were contributed for the promotion of good governance in the public sectors significantly and positively The management support of internal audit roles was positively related with the good governance but its contribution for the good governance was statistically not significance However the risk management and control role of internal audit was negatively related with the good governance and its contribution for the good governance was not statistically significant All of these five independent variables are making 38 6 of the contributions for the promotion of good governance in the public sector offices The internal auditors of Jimma zone were recommended to act in line with the purpose authority and responsibility of internal audit defined formally in their charter The institutions should involve internal audit team in the formal reporting Finally the Jimma zone finance and economic development office were recommended to support the internal audit works by hiring sufficient number of internal audito
Keywords: internal audit; good governance; role of internal audit; jimma zone